Agronomic Traits of Corn Fertilized with Sewage Sludge - de Macedo, Fernando Giovannetti [UNESP]; de Melo, Wanderley Jose [UNESP]; Souza Merlino, Luciana Cristina [UNESP]; Ribeiro, Marina Hernandez [UNESP]; Camacho, Marcos Antonio; Peruca de Melo, Gabriel Mauricio (Taylor & Francis Inc, 2012)
Although research on the environmental impacts of using waste as a fertilizer is of great importance, the basic principle for using a product as fertilizer is that it should provide nutrients for plants without causing any harm to them. The objective of this study was to evaluate the agronomic traits (number of nodes, plant height, leaf number, yield, and protein content of grains) and the nutritional status of corn treated with sewage sludge. The experiment was conducted in the municipality of Jaboticabal in a Red Latosol. A randomized block design with four treatments (0, 55, 110, and 167.5 Mg ha(-1) of sewage sludge) and five repetitions was used. At 30 days after emergence (DAE), the dose of 110 Mg ha(-1) dry weight presented greater values for plant height, leaf number and stem diameter. At 60 DAE, the treatments did not affect the agronomic traits. No influence from the treatments tested was observed for protein content of grains and yield. The dose of 167.5 Mg ha(-1) showed greater weight of 100 seeds. All treatments showed nutritional imbalances. This study confirmed the agricultural potential of sewage sludge as a source of nutrients.
Keywords: Corn; Sewage sludge; urban sludge